Occurrence and ecological implication of a tropical anguillid eel, Anguilla marmorata, in Brunei Darussalam, Borneo Island - Zan, Nur Dhabita; Sarbini, Ain; Taha, Hussein; Tan, Iy Vonne; Azri, Azie; Kahar, Rafhiah; Metali, Faizah; Ahmad, Norhayati; Arai, Takaomi (Zoologia, 2020)
Tropical anguillid eels account for two-thirds of the 19 species in Anguilla Schrank, 1798. However, information on the species diversity, geographical distribution, and life histories of the tropical eels is very limited. Recent studies suggested that morphological species identification of the tropical anguillid eels should be validated by molecular analysis for accurate identification. After surveying for three years, two anguillid eels were found in Brunei Darussalam, Borneo Island. They were firstly identified as Anguilla marmorata Quoy & Gaimard, 1824 using morphological analysis and further gene analysis of cytochrome c oxidase subunit I (COI) confirmed the species identification. This study is the first comprehensive description of A. marmorata in Brunei Darussalam, Borneo Island. Furthermore, it is also the first study to validate two anguillid eels collected from the tropical Bonin Islands of Japan as A. marmorata by means of morphological and COI analyses. The molecular phylogenetic tree and haplotype network analyses suggest that A. marmorata found in Brunei Darussalam would belong to the North Pacific population of the westernmost distribution.